The effects of stocking density on physiological traits in Holothuria forskali broodstock. (24th November 2020) - Sousa, João; Félix, Pedro M.; Brito, Ana C.; Venâncio, Eliana; Azevedo e Silva, Francisco; Simões, Tomás; Raposo, Andreia; Neves, Marta; Narciso, Luís; Melo, Ricardo; Pombo, Ana
Abstract: The high demand of sea cucumbers in international markets, mostly based in Asia, has left a deep impact on the natural stock of many species, leading to an investment in aquaculture techniques in order to mitigate these impacts. This study aimed to determine the effects of stock density in rearing broodstock of Holothuria ( Panningoturia ) forskali Delle Chiaje, 1823, a common species in the Mediterranean Sea and eastern Atlantic with commercial value. To do so, two different density treatments were selected: 1 kg/m 2 and 2 kg/m 2 . The trial took place over five months and individuals were fed a mixture of frozen microalgae ( Tetraselmis sp. and Phaeodactylum tricornutum ). At the end of the trial, the effects of stock density on the individuals' condition were assessed by analysing different variables, namely their fresh and gutted weight, evisceration and mortality rates, gonadosomatic index and oocyte size and even biochemical content, such as protein and lipid content in muscle bands. No significant differences were found between density treatments regarding any of the parameters assessed, aside from mean oocyte diameter. Individuals from the lower‐density treatment presented a smaller mean oocyte diameter, supplied with fewer oocytes, than individuals in both the higher‐density treatment and the baseline group. Regardless of this one difference, all trial individuals were able to maintain their elevated gonadal developmental stage for a full period of five months past their reproductive peak, with female holothurians subjected to the higher‐density treatment showing signs of increasing vitellogenic reserves, a considerable advantage in aquaculture broodstock rearing.